In Vitro Cytotoxicity Evaluation Of Processed Natural Coral On Human Fibroblast And Osteoblast Cell Lines - Omar, Nor Shamsuria (2010)
The aim of this study was to evaluate the in vitro cytotoxicity of the locally produced processed natural coral (Health Campus, Universiti Sains Malaysia) from the Porites species in terms of proliferation, apoptosis study and cell attachment by using human osteoblast (HOS) and fibroblast (MRC-5) cell lines (ATCC, USA). The in vitro cytotoxicity of the processed natural coral (PNC) was evaluated using test on extract and direct contact as per ISO 10993-5 (1999). HOS cells were used to study the magnitude of proliferation when exposed to the extraction medium of two different particle sizes of PNC, granules (0.5-1mm) and powder (1-50μm).